Effectiveness of Cognitive Restructuring in the Management of Mathophobia Among Secondary School Students in Khana L.G.A of Rivers State, Nigeria - Ijeoma Regina, Ernest-Ehibudu; Augustine Lezorgia, Wayii (European Scientific Journal, ESJ, 2017)
This study was developed and conducted to test the effect of cognitive restructuring in the management of mathophobia (that is, Mathematics anxiety) among secondary school students in Khana Local Government Area of Rivers State, Nigeria. To guide the study, two research questions and two null hypotheses were formulated for testing at 0.05 level of significance. In executing the study, the pre-test, post-test, and control group experimental research design was adopted using a randomized sample of 120 SS2 students drawn from three public secondary schools only. The researchers developed an instrument titled â€œMathematics Diagnostic Questionnaireâ€ (MDQ) which was adequately assessed for validity and reliability and was used in collecting pre-test and post-test data for the cognitive restructuring and control groups. Data analysis was done using mean, and standard deviation for the research questions, while independent sample and paired sample t-test were used for the hypotheses. The result obtained showed that the cognitive restructuring was significantly effective in the management of mathophobia among secondary school students. There is a slight reduction in the effect of cognitive restructuring during follow-up; there is a statistical significant difference in the mathophobic level of students treated with cognitive restructuring and those in the control group. Based on the major findings, recommendations were made among which is that functional guidance and counselling centers be established at all educational levels and be manned by professional counsellors who are competent in cognitive restructuring techniques to assist those who have mathophobia and other maladaptive behaviours. Suggestions for further study were made.